2020
DOI: 10.1186/s12951-020-00664-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stem cell membrane-coated isotretinoin for acne treatment

Abstract: Background: Topical isotretinoin is commonly used to treat acne. However, topical isotretinoin has side effects and can hardly permeate through the stratum corneum, the most important skin barrier. Therefore, this study aimed to demonstrate the efficacy of nanoparticles as stable carriers with great curative effects, low side effects, and strong transdermal ability. Results: In a rabbit model of hyperkeratinization, STCM-ATRA-NPs showed significant therapeutic efficacy. By contrast, negative therapeutic effica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…These stem cell-like microparticles (MPs) exhibited similar surface antigens and secretomes to those of genuine stem cells. They could promote cardiomyocyte functions and showed cryopreservation and stability with lyophilization and could also avoid the tumorigenicity and immunogenicity risks of living stem cell transplantation [100]. Direct injection of these MPs in an animal model of acute MI could promote angiogenesis and alleviate ventricle remodelling.…”
Section: Stem Cell-mimetic Cell Membrane-based Therapymentioning
confidence: 99%
“…These stem cell-like microparticles (MPs) exhibited similar surface antigens and secretomes to those of genuine stem cells. They could promote cardiomyocyte functions and showed cryopreservation and stability with lyophilization and could also avoid the tumorigenicity and immunogenicity risks of living stem cell transplantation [100]. Direct injection of these MPs in an animal model of acute MI could promote angiogenesis and alleviate ventricle remodelling.…”
Section: Stem Cell-mimetic Cell Membrane-based Therapymentioning
confidence: 99%
“…Following publication of our article [ 1 ] the authors found that some of the images in the publication had been misused, so that three images presented at high magnification did not correspond to those at low magnification. The correct images for Figure 3b, Figure 4 (Treatment efficiency on hyper keratinization model by H&E staining—Group Blank H&E × 40) and Figure 7a are shown below.…”
Section: Correction To: J Nanobiotechnol (2020) 18:106 101186/s12951-020-00664-9mentioning
confidence: 99%
“…Small particle size facilitates dermal drug delivery, penetrates deeper into the skin, and improves transdermal transport into and across the skin barrier for enhanced transdermal transport ( Alvarez-Román et al, 2004 ; Ji et al, 2021 ). Our preliminary research found that cell membrane drug-carrying technology could be used to modify nanoparticles (NPs) so that they gain the functions and properties unique to cell membranes, improving their biocompatibility and targeting, with good transdermal, low irritation, and slow release properties ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%